Methods of phase, chain analysis and calculation of electric consumption of complex objects with interproduction relations - Alimov A.A., Ruzinazarov M.R. ,Mahmutkhonov, S.K., Uzakov В. (International Journal of Advanced Science and Technology, 2020)
In article questions of calculation of power consumption of complex objects of the industrial enterprises are considered. The technique of stage-by-stage and chain analysis of calculation of electric consumption of complex objects with interproduction links is offered. The calculation scheme of internal and external interproduction links of the plant is described.